Collaborative Governance Process in Supporting Smart Living in Pekanbaru City - Ayu Tri Utami; Adianto Adianto; Mayarni Mayarni (Publica: Jurnal Pemikiran Administrasi Negara, 2022)
This research is motivated by the background of waste management in the city of Pekanbaru, where waste handling has not been optimally carried out. The waste problem can have an impact on social, economic, health and environmental aspects and even cause the greenhouse effect which is the cause of climate change. This condition is exacerbated by the government's inability to provide environmental management facilities, low awareness and participation of the community, involvement of the private sector, human resource issues, budget and compliance with regulations. Overcoming this, the Collaborative Governance process is carried out in creating a clean environment, this is a form of one of the pillars of the smart city of Pekanbaru City, namely smart living. The purpose of this research is to find out the process of collaborative governance in supporting smart living in the city of Pekanbaru. This study uses qualitative methods with data collection techniques in this study based on the results of interviews, observations, and documentation. While the data analysis technique consists of several stages, namely data transcription, categorization, verification, as well as interpretation and description. This research was conducted at the Pekanbaru City Environment and Sanitation Service and PT. PJB Ubjom Tenayanraya, Pekanbaru. The results of this study indicate that the collaborative governance process carried out is quite well implemented in an effort to handle waste management in Pekanbaru City based on the collaboration process cycle according to Ansel and Gash called face to face dialogue, building trust, building commitment, sharing understanding, and intermediate outcomes.